Sustainable water management in an upstream watershed under transboundary eco-compensation policy: a bi-level robust optimization model - Linhuan He; Yee Van Fan; Yuhong Shuai; Liming Yao; Petar Sabev Varbanov; Ting Pan (Journal of Hydrology, 2026)

Multi-dimensional metabolic engineering and enzyme engineering in Escherichia coli for highly efficient biosynthesis of 2,5-furandicarboxylic acid - Yanan Cui; Peiyi Zhang; Renjie Miao; Mengqi Zhao; Liqiang Fan; Xu Li; Yongjun Qiu; Chen Deng; Liming Zhao (Bioresource Technology, 2026)

Keap1/Nrf2 mediated ferroptosis in early-life lead exposure-induced cognitive dysfunction in mice - Feiyu Zhao; Liming Huang; Binbin Yang; Ruokun Wei; Fan Qiao; Zihao Qi; Huishuai Li; Zhenning Li; Yuanyuan Fang; Dongjie Peng; Shaojun Li (NeuroToxicology, 2026)

Experimental study on the seismic performance of high-fill embankment slopes reinforced with basalt fiber geogrid - Jing Lian; Jie Fan; Zhengsong Xiang; Mingduan Liu; Liming Qu; Xuanming Ding (Soil Dynamics and Earthquake Engineering, 2026)

Nonlinear dynamics and optimal deployment of a deep-ocean mining riser with surface-mounted flow-disturbing robots - Shanfei Fan; Xiaoqiang Guo; Kelun Yang; Reza N. Jazar; Edson Denis Leonel; Nerguibaatar Tsend; Xianbin Liu; Yuwen Wang; Liming Dai; Jun Liu; Ning Zong; He Chen; et al. (Ocean Engineering, 2026)

Triboelectric-motorized electromagnetic conversion enables frequency upconversion and impedance reduction for low-frequency mechanical energy harvesting - Tingyu Wang; Lihua Wang; Ai Chen; Bocheng Chen; Liming Tan; Junyin Cheng; Fan Xu; Huiyuan Wu; Kaixian Li; Yilan Zhang; Yuqing Wen; Haixuan Gan; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal Dynamics of Dissolved CO₂ and N₂O in Yangtze River Delta: Identifying Drivers and Environmental Controls - Yanjie Wei; Fei Sun; Xuexue Fan; Zhangmu Jing; Heran Zhang; Jiao Geng; Shengqiang Tu; Liming Xue; Peng Yuan (Water, Air, & Soil Pollution, 2026)

Post-synthetic modification strategy for constructing dual-emission fluorescent sensor toward visual detection and quantification of 3-nitrotyrosine biomarker - Liying Liu; Yun Zhou; Jiayuan Liu; Yujie Zhao; Yuhua Gao; Mohd Muddassir; Xiutang Zhang; Liming Fan (Analytica Chimica Acta, 2026)

Epigenetic impacts of the acaricide flumethrin on honeybees (Apis mellifera) - Xue Wang; Suzhen Qi; Mu Ding; Wei Zhang; Aidi Huang; Changlu Sun; Man Fan; Liming Wu; Miao Wang (Environmental Pollution, 2026)

Sustainable multifunctional packaging films based on chitosan and food waste-derived carbon nanodots for fruit preservation - Ying Ren; Dan Chen; Shiyu Lin; Xiaoping Fan; Liming Cao (Journal of Food Engineering, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

A dual-gradient Janus architecture: Engineering aerogel sensors with high sensitivity and wide linear range for human-machine interaction - Xianghui Zeng; Yao Lu; Junwei He; Liming Zou; Zezhao Ding; Yang Fan; Yan Vivian Li (Chemical Engineering Journal, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Echinacoside ameliorates bleomycin-induced idiopathic pulmonary fibrosis by regulating macrophage polarization - Yifan Zhang; Liming Fan; Mengni Wang (Journal of Molecular Histology, 2026)

Real-time Monitoring Unveils Three Distinct Neuronal Response Patterns to SAW Ultrasound via L-type Calcium Channels - Yiming Chen; Wenxu Tang; Yifan Wang; Ya Gao; Jiaqi Hu; Yixuan Lu; Long Meng; Hairong Zheng; Yi Feng; Liming Cheng; Wenyong Fan; Qian Cheng; et al. (Neuroscience Bulletin, 2026)

Design and synthesis of bis(indolyl)-hydrazide-hydrazone derivatives and their antifungal activities against plant pathogen fungi - Haowei Huang; Jinrui Tang; Kunrong Dang; Jiayue Tang; Enxian Li; Liming Fan; Min Ye; Guoxing Wu; Fawu Su (Natural Product Research, 2025)

Comprehensive characterization of cold plasma/nanoparticles-functionalized gelatin active film and its application in tilapia fillets - Tingting Yang; Xinming Zhang; Chenhan Huang; Guanghua Xia; Haohao Shi; Xueying Zhang; Fan Wang; Liming Zhang; Jiamei Wang (Food Research International, 2025)

Moisture-adaptive cellulose/MXene aerogels for synergistic moisture and triboelectric energy harvesting - Jiwei Zhang; Xinran Zhou; Mengjie Wu; Liming Zhu; Zechang Ming; Weikang Li; Yong Xia; Hao Liu; Zijie Zhou; Tao Zhang; Minghui Fan; Jianyong Yu; et al. (Chemical Engineering Journal, 2025)

Yeast-activated carbon/montmorillonite nanosheets with porous spherical shells for efficient tetracycline degradation - Liming Wu; Zhongyu Su; Jinzhou Fan; Daoguang Teng; Weijun Peng; Wei Wang; Yijun Cao (Applied Clay Science, 2025)

Emission characteristics of VOCs from the typical spent lithium-ion battery recycling industry - Lei Zhou; Fengbin Ji; Zhiling Wang; Junkang Fan; Heng Chen; Manyun Xu; Zhe Liu; Liming Yang; Xubiao Luo (Journal of Hazardous Materials, 2025)

Defect-engineered indium–organic framework displays the higher CO2 adsorption and more excellent catalytic performance on the cycloaddition of CO2 with epoxides under mild conditions - Meiyu Ren; Bo Zhao; Chong Li; Yang Fei; Xiaotong Wang; Liming Fan; Tuoping Hu; Xiutang Zhang (Molecular Diversity, 2025)

Urbanization enhances soil nitrogen mineralization mainly by increasing particulate organic nitrogen fractions in urban park greenspaces: A case study in Hangzhou, China - Bo Fan; Yuye Shen; Yan Wang; Liming Yin; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Applied Soil Ecology, 2025)

Heterogeneous zebra-patterned ultra-sensitive flexible sensor for human motion detection and game control - Xianghui Zeng; Yao Lu; Liming Zou; Zirui Pu; Deqiang Chen; Zezhao Ding; Yang Fan; Yanli Wang; Yan Vivian Li (Chemical Engineering Journal, 2025)

O-O bridge adsorption catalysis of different metal single atoms toward high-sensitive detection of H2O2 - Juan Li; Jinggao Wu; Fan Shi; Mingyuan Wang; Zhuo Zou; Zhisong Lu; Liming Dai; Chang Ming Li (Chemical Engineering Journal, 2025)

Actual Truck Arrival Prediction at a Container Terminal with the Truck Appointment System Based on the Long Short-Term Memory and Transformer Model - Mengzhi Ma; Xianglong Li; Houming Fan; Li Qin; Liming Wei (Journal of Marine Science and Engineering, 2025)
The implementation of the truck appointment system (TAS) in various ports shows that it can effectively reduce congestion and enhance resource utilization. However, uncertain factors such as traffic and weather conditions usually prevent the external trucks from arriving at the port on time according to the appointed period for container pickup and delivery operations. Comprehensively considering the significant factors associated with truck appointment no-shows, this paper proposes a deep learning model that integrates the long short-term memory (LSTM) network with the transformer architecture based on the cascade structure, namely the LSTM-Transformer model, for actual truck arrival predictions at the container terminal using TAS. The LSTM-Transformer model combines the advantages of LSTM in processing time dependencies and the high efficiency of the transformer in parsing complex data contexts, innovatively addressing the limitations of traditional models when faced with complex data. The experiments executed on two datasets from a container terminal in Tianjin Port, China, demonstrate superior performance for the LSTM-Transformer model over various popular machine learning models such as random forest, XGBoost, LSTM, transformer, and GRU-Transformer. The root mean square error (RMSE) values for the LSTM-Transformer model on two datasets are 0.0352 and 0.0379, and the average improvements are 23.40% and 18.43%, respectively. The results of sensitivity analysis show that possessing advanced knowledge of truck appointments, weather, traffic, and truck no-shows will improve the accuracy of model predictions. Accurate forecasting of actual truck arrivals with the LSTM-Transformer model can significantly enhance the efficiency of container terminal operational planning.

Bioenergy recovery and carbon emissions benefits of short-term bio-thermophilic pretreatment on low organic sewage sludge anaerobic digestion: A pilot-scale study - Hui Wang; Xiang Fu; Haozhe Huang; Danni Shen; Dongdong Fan; Liming Zhu; Xiaohu Dai; Bin Dong (Journal of Environmental Sciences, 2025)

Weighted comprehensive risk assessment and pollution analysis of long-term printing and dyeing sludge landfills in an industrialized Chinese city - Qian Xiang; Dongdong Fan; Liming Zhu; Tongsheng Zhang; Danni Shen; Hui Wang; Bin Dong (Environmental Pollution, 2025)

A Meta‐Analysis of Bycatch Mitigation Methods for Sea Turtles Vulnerable to Swordfish and Tuna Longline Fisheries - Hao Yan; Cheng Zhou; Eric Gilman; Jie Cao; Rong Wan; Fan Zhang; Jiangfeng Zhu; Liuxiong Xu; Liming Song; Xiaojie Dai; Siquan Tian (Fish and Fisheries, 2025)
Fisheries bycatch poses one of the most significant threats to sea turtles. Although various methodologies have been developed to mitigate sea turtle bycatch in swordfish and tuna longline fisheries, the effectiveness and interactions remain uncertain. In this study, we conducted a comprehensive meta‐analysis, encompassing 41 studies focused on sea turtles and 36 studies on tunas, swordfish and sharks, all derived from well‐controlled experimental research in swordfish and tuna longline fisheries. The objective was to systematically evaluate the relative effectiveness of species‐specific mitigation strategies for sea turtles, particularly examining the impact of circle hooks and fish bait as alternatives to conventional longline fishing practices. While a nuanced hierarchy, characterised by species‐specific patterns, was observed among the mitigation measures, circle hooks demonstrated great promise in reducing bycatch of loggerhead, olive ridley and leatherback turtles, with minimal impact on the catch rates of tuna, swordfish and sharks. We highlighted the broader applicability of fish bait in minimising sea turtle bycatch, noting that the effectiveness of bait may overlap with that of hooks, potentially making the additional benefits of the hooks less evident. The study also revealed regional variations in the effectiveness of these methods, emphasising the need for more detailed data collection. Given current data limitations that restrict extensive meta‐analyses, a series of small‐sample studies with promising innovations, exemplified by circle hooks with a wire appendage and blue‐white lights, necessitates in‐depth investigation and field tests.

Organic carbon burial dynamics at the Chukchi Shelf margin: Implications for the Arctic Ocean carbon sink - Liming Ye; Xiaoguo Yu; Yanguang Liu; Anatolii S. Astakhov; Alexander Bosin; Yeping Bian; Linsen Dong; Weijia Fan; Haili Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

An investigation on synergistic effects and kinetic characteristics of pyrolysis of kitchen waste components: Starch, protein and lipid - Liming Yao; Benteng Wu; Honggang Fan; Jing Gu; Haoran Yuan; Jun Xie (Journal of Environmental Chemical Engineering, 2024)

Evaluating drought stress response of poplar seedlings using a proximal sensing platform via multi-parameter phenotyping and two-stage machine learning - Xuexing Fan; Huichun Zhang; Lei Zhou; Liming Bian; Xiuliang Jin; Luozhong Tang; Yufeng Ge (Computers and Electronics in Agriculture, 2024)

Construction of negative electrostatic sugared gourd pore within nickel-based metal-organic framework for one-step purification acetylene from ethylene and carbon dioxide mixture - Xing-Zhe Guo; Bing Lin; Guang-Zu Xiong; Rajamani Krishna; Zhao-Rong Zhang; Qing-Zan Liu; Zhi-Xiong Zhang; Liming Fan; Jie Zhang; Bingwen Li (Chemical Engineering Journal, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

A multiplex method for the detection of food microorganisms based on suspension microarrays combined with recombinase-aided amplification - Wentao Zeng; Xihao Fan; Azadeh Nilghaz; Gengfen Zhao; Lingfeng Yan; Zhuoxuan Lu; Liming Zhang (Food Bioscience, 2024)

Genome-wide CRISPR screening identifies critical role of phosphatase and tensin homologous (PTEN) in sensitivity of acute myeloid leukemia to chemotherapy - Liming Lin; Jingjing Tao; Ying Meng; Yichao Gan; Xin He; Shu Li; Jiawei Zhang; Feiqiong Gao; Dijia Xin; Luyao Wang; Yili Fan; Boxiao Chen; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Resourceful application and mechanism of oyster shell-microalgae synergistic system：Sustainable treatment of harsh low carbon nitrogen ratio actual wastewater - Yanni Geng; Liming Yang; Chun-Ang Lian; Spyros G. Pavlostathis; Zhiguang Qiu; Zhensheng Xiong; Yuanqi Liu; Bing Li; Jincheng Hu; Wenbo Fan; Xubiao Luo; Ke Yu (Environmental Research, 2024)

Fe-doped CeTiOx catalysts facilitate the oriented oxidation of NO to achieving simultaneous desulfurization and denitration in a WFGD system - Lei Zhou; Zhixiang Wei; Junkang Fan; Qingqing Yu; Chuang Zhao; Jie Zhang; Liming Yang; Weili Dai; Linjun Yang (Fuel, 2024)

Co4+ in porous ZIF-67-derives intercalating-bridging adsorption of 2-reaction sites for simultaneous 2-electron transfer toward sensitive detection of uric acid - Li Peng Gan; Juan Li; Fan Shi; Zhuo Zou; Ke Jiang Li; Zhuan Zhuan Shi; Xiao Shuai Wu; Yun Peng Li; Wei Sun; Zhi Song Lu; Tao Hu; Liming Dai; et al. (Analytica Chimica Acta, 2024)

A high-throughput DNA analysis method based on isothermal amplification on a suspension microarray for detecting mpox virus and viruses with comparable symptoms - Liming Zhang; Jieyu Liu; Shisi Huang; Wentao Zeng; Li Li; Xihao Fan; Zhuoxuan Lu (Analytica Chimica Acta, 2024)

Numerical investigation of interaction between anticyclonic eddy and semidiurnal internal tide in the northeastern South China Sea - Liming Fan; Hui Sun; Qingxuan Yang; Jianing Li (Ocean Science, 2024)
We investigate the interaction between an anticyclonic eddy (AE) and semidiurnal internal tide (SIT) on the continental slope of the northeastern South China Sea (SCS), using a high spatiotemporal resolution numerical model. Two key findings are as follows: first, the AE promotes energy conversion from low-mode to higher-mode SIT. Additionally, production terms indicate that energy is also transferred from the SIT field to the eddy field at an average rate of 3.0 mW m−2 (accounting for 7 % of the incoming energy flux of SIT when integrated over the eddy diameter). Second, the AE can modify the spatial distribution of tidal-induced dissipation by refracting, scattering, and reflecting low-mode SIT. The phase and group velocities of the SIT are significantly influenced by the eddy field, resulting in a northward or southward shift in the internal tidal rays. These findings deepen our understanding of the complex interactions between AE and SIT, as well as their impacts on energy conversion, wave propagation, and coastal processes.

The low dose of L-lactic acid as loess soil amendment enhances wheat rhizosphere microecosystem - Wenwen Chen; Pinjing He; Hua Zhang; Haowen Duan; Liming Shao; Fan Lü (Rhizosphere, 2023)

Machine learning aids solvothermal liquefaction of algal biomass: Prediction of nitrogen content and bio-oil yield - Oraléou Sangué Djandja; Ya-Qi Shan; Liming Fan; Yu Wu; Adekunlé Akim Salami; Xuebin Lu; Pei-Gao Duan; Shimin Kang (Fuel, 2023)

Hydrogen peroxide oxidation modifies the structural properties and allergenicity of the bee pollen allergen profilin - Enning Zhou; Weiwei Wang; Xiaofeng Xue; Pianpian Wang; Fan Wu; Liming Wu; Qiangqiang Li (Food Chemistry, 2023)

Seismic and hydrological triggers for a complex cascading geohazard of the Tianmo Gully in the southeastern Tibetan Plateau - Rui Guo; Liming Jiang; Zhida Xu; Chao Li; Ronggang Huang; Zhiwei Zhou; Tao Li; Yi Liu; Hansheng Wang; Xuanmei Fan (Engineering Geology, 2023)

Design and fabrication of rewritable surfaces with high durability - Lei Zhang; Yuying Fan; Jie Xie; Xinqiao Lai; Taoyan Mao; Jianguo Zhang; Guojie Zhang; Liming Wang (Chemical Engineering Journal, 2023)

Environmental and economic assessment of the construction, operation, and demolition of a decentralized composting facility - Liao Nanlin; Lü Fan; Zhang Hua; Shao Liming; He Pinjing (Science of The Total Environment, 2023)

A critical review on odor measurement and prediction - Yujing Wang; Liming Shao; Xinyue Kang; Hua Zhang; Fan Lü; Pinjing He (Journal of Environmental Management, 2023)

Highly effective recovery of palladium from a spent catalyst by an acid- and oxidation-resistant electrospun fibers as a sorbent - Nianshou Cheng; Lin Zhang; Mingyue Wang; Jiancheng Shu; Penghui Shao; Liming Yang; Xiaojing Meng; Yuzhu Fan; Min Li (Chemical Engineering Journal, 2023)

Upcycling of real-world HDPE plastic wastes into high-purity methane and hierarchical porous carbon materials: Influence of plastics additives - Xiaoli Zhou; Pinjing He; Wei Peng; Fan Lü; Liming Shao; Hua Zhang (Journal of Environmental Chemical Engineering, 2023)

Molecular behavior and interactions with microbes during anaerobic degradation of bio-derived DOM in waste leachate - Junjie Qiu; Tianqi Li; Fan Lü; Yulong Huang; Chao Li; Hua Zhang; Liming Shao; Pinjing He (Journal of Environmental Sciences, 2023)

De novo biosynthesis of 2′-fucosyllactose in engineered Pichia pastoris - Difan Qian; Chunyue Zhang; Chen Deng; Mian Zhou; Liqiang Fan; Liming Zhao (Biotechnology Letters, 2023)

Chemical composition and therapeutic mechanism of Xuanbai Chengqi Decoction in the treatment of COVID-19 by network pharmacology, molecular docking and molecular dynamic analysis - Liming Fan; Shuai Feng; Ting Wang; Xinli Ding; Xinxin An; Zhen Wang; Kun Zhou; Minjuan Wang; Xifeng Zhai; Yang Li (Molecular Diversity, 2023)

Growth Performance of Complete Diallel Crosses Among New Varieties of Chinese Pearl Oyster Pinctada martensii - Chao Fan; Xuekai Zhang; Xingzhi Zhang; Shaobo Yue; Yangchun Li; Liming Tang; Qiongzhen Li; Zhaoping Wang (Journal of Ocean University of China, 2023)

Antimicrobial peptides from marine animals: Sources, structures, mechanisms and the potential for drug development - Shuocun Wang; Liming Fan; Hanyu Pan; Yingying Li; Yan Qiu; Yiming Lu (Frontiers in Marine Science, 2023)
The emergence of antibiotic-resistant bacteria has become a major challenge in current clinical treatment. As essential natural molecules involved in innate immunity, antimicrobial peptides (AMPs) have the potential to break the limits of antibiotic resistance. While AMPs are widely presented in various organisms on this planet, the marine environment is unique in generating a large number of AMPs that exhibit characteristic structures and functions. This review summarizes the structures and mechanisms of action of AMPs derived from invertebrates, fish, amphibians, reptiles, and mammals in the ocean. The comparison of AMPs from organisms in different habitats demonstrates the preference of Arg (arginine) and Leu (leucine) in marine AMPs, which might be associated with the adaptation to the unique features of bacterial membranes in marine environments. In addition, the potential and applications of marine AMPs for the development of novel antibiotics are also described. These summaries are expected to provide a reference for the development and utilization of marine resources in drug development or aquiculture.

Odor emission rate of a municipal solid waste sanitary landfill during different operation stages before final closure - Wanting Du; Fan Lü; Hua Zhang; Liming Shao; Pinjing He (Science of The Total Environment, 2023)

Pressure characteristics of the fuel system for two-stroke diesel engines under different operational modes - Yun Bai; Qi Lan; Liyun Fan; Jing Yao; Xiangdong Kong; Liu Yang; Liming Wen (Fuel, 2023)

Electron exchange capacities of colloidal biochar: Affected by spatial structure distribution instead of particle size - Shasha Li; Fan Lü; Hua Zhang; Liming Shao; Pinjing He (Chemical Engineering Journal, 2023)

The involvement of oxidative stress, neuronal lesions, neurotransmission impairment, and neuroinflammation in acrylamide-induced neurotoxicity in C57/BL6 mice - Mengyao Zhao; Linlin Deng; Xiaoxuan Lu; Liqiang Fan; Yang Zhu; Liming Zhao (Environmental Science and Pollution Research, 2022)

Study on the Effect of Mass Selection and Hybridization on Growth Performance of Chinese Pearl Oyster Pinctada martensii - Chao Fan; Xuekai Zhang; Liming Tang; Xingzhi Zhang; Jinlong Li; Yangchun Li; Qiongzhen Li; Zhaoping Wang (Frontiers in Marine Science, 2022)
The pearl oyster Pinctada martensii is an important species for sea pearl production in China. To explore the influence of the combination of mass selection and hybridization on growth performance of P. martensii , we established four selected groups and four control groups (each with two within-family crosses and two reciprocal hybrid crosses) using 1-year-old offspring of two families (Family A and Family B) from Beihai, Guangxi Province, China. Generally, the growth of the selected group was greater than that of the control group for both within-family crosses and reciprocal hybrid crosses. Shell length and width were affected by genotype, environmental factors, and the interaction between the two on Days 210 and 360. The shell widths of the four reciprocal hybrid crosses all showed heterosis on Day 360. The four within-family crosses showed a certain degree of inbreeding depression during the growth period. On Day 360, the three genetic parameters for shell width of the selected group of ♀ Family B and ♂ Family A were the largest, with values of 0.70, 1.17, and 0.06 for realized heritability, standard response to selection, and current genetic gain, respectively. Overall, the growth performance of ♀ Family B × ♂ Family A in the selected group was the best. Therefore, the combination of mass selection and hybridization could be an effective way to improve the growth performance of P. martensii .

Retraction Note to: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2022)

High-frequency interference waves in low strain dynamic testing of X-section concrete piles - Liming Qu; Yuming Fan; Xuanming Ding; Changwei Yang; Yanling Zhang (Earthquake Engineering and Engineering Vibration, 2021)

Leaching behavior of phosphorous compounds from sewage sludge ash based on quantitative X-ray diffraction analysis - Pinjing He; Xiaotong Zhang; Fan Lü; Liming Shao; Hua Zhang (Waste Disposal & Sustainable Energy, 2020)

The Potential Vertical Distribution of Bigeye Tuna (Thunnus obesus) and Its Influence on the Spatial Distribution of CPUEs in the Tropical Atlantic Ocean - Shenglong Yang; Liming Song; Yu Zhang; Wei Fan; Bianbian Zhang; Yang Dai; Heng Zhang; Shengmao Zhang; Yumei Wu (Journal of Ocean University of China, 2020)

Synthesis and antifungal activity of carvacrol and thymol esters with heteroaromatic carboxylic acids - Kaibo Wang; Shanshan Jiang; Yunhai Yang; Liming Fan; Fawu Su; Min Ye (Natural Product Research, 2019)

Efficient inhibition of Cronobacter biofilms by chitooligosaccharides of specific molecular weight - Jun Lu; Qiming Chen; Bolin Pan; Zhen Qin; Liqiang Fan; Quanming Xia; Liming Zhao (World Journal of Microbiology and Biotechnology, 2019)

Chitooligosaccharide plays essential roles in regulating proline metabolism and cold stress tolerance in rice seedlings - Yang Zhang; Liqiang Fan; Mengyao Zhao; Qiming Chen; Zhen Qin; Zhihang Feng; Toru Fujiwara; Liming Zhao (Acta Physiologiae Plantarum, 2019)

Antifungal activity of phenolic monoterpenes and structure-related compounds against plant pathogenic fungi - Kaibo Wang; Shanshan Jiang; Te Pu; Liming Fan; Fawu Su; Min Ye (Natural Product Research, 2019)

RETRACTED ARTICLE: Revisiting the male genetic landscape of China: a multi-center study of almost 38,000 Y-STR haplotypes - Michael Nothnagel; Guangyao Fan; Fei Guo; Yongfeng He; Yiping Hou; Shengping Hu; Jiang Huang; Xianhua Jiang; Wook Kim; Kicheol Kim; Chengtao Li; Hui Li; et al. (Human Genetics, 2017)

Ecological effects of rice-duck integrated farming on soil fertility and weed and pest control - Qing Teng; Xue-Feng Hu; Chang Cheng; Zhiqing Luo; Fan Luo; Yong Xue; Yijun Jiang; Zhen Mu; Liming Liu; Minyong Yang (Journal of Soils and Sediments, 2016)

Real-Time Tracking Method for a Magnetic Target Using Total Geomagnetic Field Intensity - Liming Fan; Chong Kang; Xiaojun Zhang; Shengwei Wan (Pure and Applied Geophysics, 2016)

Influences of introducing frogs in the paddy fields on soil properties and rice growth - Qing Teng; Xue-Feng Hu; Fan Luo; Chang Cheng; Xinyi Ge; Minyong Yang; Liming Liu (Journal of Soils and Sediments, 2016)

Sequence characterization and computational analysis of the non-ribosomal peptide synthetases controlling biosynthesis of lipopeptides, fengycins and bacillomycin D, from Bacillus amyloliquefaciens Q-426 - Pengchao Zhao; Chunshan Quan; Liming Jin; Lina Wang; Xinjuan Guo; Shengdi Fan (Biotechnology Letters, 2013)

Secretory/releasing proteome-based identification of plasma biomarkers in HBV-associated hepatocellular carcinoma - Lei Yang; WeiQi Rong; Ting Xiao; Ying Zhang; Bin Xu; Yu Liu; LiMing Wang; Fan Wu; Jun Qi; XiuYing Zhao; HongXia Wang; NaiJun Han; et al. (Science China Life Sciences, 2013)

Effects of critical medium components on the production of antifungal lipopeptides from Bacillus amyloliquefaciens Q-426 exhibiting excellent biosurfactant properties - Pengchao Zhao; Chunshan Quan; Liming Jin; Lina Wang; Jianhua Wang; Shengdi Fan (World Journal of Microbiology and Biotechnology, 2013)

Ectopic Expression of AtCIPK23 Enhances Tolerance Against Low-K+ Stress in Transgenic Potato - Xiyao Wang; Jia Li; Xue Zou; Liming Lu; Liqin Li; Su Ni; Fan Liu (American Journal of Potato Research, 2011)

An Experimental Study of Mobilization and Creeping Flow of Oil Slugs in a Water-Filled Capillary - Mingzhe Dong; Quiliang Fan; Liming Dai (Transport in Porous Media, 2009)

Clinical doses of amikacin provide more effective suppression of the human CFTR-G542X stop mutation than gentamicin in a transgenic CF mouse model - Ming Du; Kim M. Keeling; Liming Fan; Xiaoli Liu; Timea Kovaçs; Eric Sorscher; David M. Bedwell (Journal of Molecular Medicine, 2006)